Prevalence of peste des petits ruminants in the arid zone in the Republic of Niger - FAROUGOU, SOUAÏBOU; GAGARA, MARIAMA; MENSAH, GUY APOLLINAIRE (My University, 2013)
The study aimed to determine the prevalence of peste des petits ruminants in the arid zone (Niamey, Tillabéry and Tahoua) of the Republic of Niger. A serological survey was conducted and 519 serum samples were collected from 253 unvaccinated sheep and 266 unvaccinated goats. The sample included 340 female animals (168 sheep and 172 goats) and 160 kids and lambs (78 lambs and 82 kids). A competitive enzyme-linked immunosorbent assay yielded an overall seroprevalence of 45.0%. The prevalence in sheep was 42.0% compared with 47.9% in goats. The seroprevalence observed amongst small ruminants in Tahoua (49.8%) and Tillabéry (46.6%) was significantly higher (p = 0.001) than that observed in animals from Niamey (25.1%). It was also higher (p = 0.04) in sheep younger than two years (51.8%) than in adults (37.6%). Conversely, the seroprevalence showed no significant difference between male animals (35.8% in sheep; 50.1% in goats) and female animals (45.1% in sheep; 46.4% in goats). The prevalence of the disease observed amongst the sheep and goat populations confirms the continued danger of this disease in the areas studied. It is therefore necessary to develop strategies such as improving livestock services, providing effective vaccines and implementing a vaccination programme for an effective control of the disease in sub-Saharan Africa.
Keywords: Prevalence; peste des petits ruminants; Niger